2022
DOI: 10.1111/coin.12522
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid optimization algorithm based feature selection for mammogram images and detecting the breast mass using multilayer perceptron classifier

Abstract: Breast cancer is the second most frequent malignant tumor in the world. Early findings of breast cancer can significantly improve treatment effectiveness. Manual methods of breast cancer diagnosis are prone to human fault and inaccuracy, and they take time. A computer-aided diagnosis can assist radiologists in making better choices by overcoming the disadvantages of manual methods. One of the significant steps in the breast cancer diagnosis process is feature selection. In recent decades, many studies have pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…Rajendran [20] implemented the hybrid optimization approach which was the combination of the grasshopper optimization algorithm (GOA) and crow search algorithm (CSA) for eliminating the optimal features. Here, the multilayer perceptron (MLP) neural network was used to perform the classification.…”
Section: Related Workmentioning
confidence: 99%
“…Rajendran [20] implemented the hybrid optimization approach which was the combination of the grasshopper optimization algorithm (GOA) and crow search algorithm (CSA) for eliminating the optimal features. Here, the multilayer perceptron (MLP) neural network was used to perform the classification.…”
Section: Related Workmentioning
confidence: 99%
“…The performance of the new approach was investigated using CIC2017, NSL-KDD, BoT-IoT, and KDD99 datasets. In 25 , Grasshopper Optimization Algorithm and the Crow Search Algorithm were hybridized to address the challenge of feature selection leading to classification using MLP. Results showed that when combined with MLP, the hybrid method returned the values of 97.1%, 98%, and 95.4% for accuracy, sensitivity and specificity, respectively, using a mammographic dataset.…”
Section: Related Workmentioning
confidence: 99%
“…Even the few studies which have considered this challenge have only applied methods using peak-inflection point, discrete cosine transform (DCT), discrete wavelet transform (DWT), singular value decomposition (SVD), staked CNN architectures, dual-stream deep architecture, dimensionality reduction like principal component analysis (PCA), feature fusion which improves features resulting from feature extraction using deep convolutional neural network (DCNN), and CNN-based auto features extraction (CNN-AFE). For example, Sahlol et al 23 applied Salp Swarm Algorithm (SESSA) to improve the selection of preferred detected features leading to the classification of White Blood Cell (WBC) Leukaemia in samples; Fatani et al 24 used the traditional method of CNN for extracting features, and then applied Aquila Optimizer (AQU) for further feature selection; in 25 , the Grasshopper Optimization Algorithm and the Crow Search Algorithm were hybridized to address the challenge of feature selection leading to classification using MLP. Whale Optimization Algorithm (WOA), which was hybridized with Flower Pollination Algorithm (FPA), was investigated in 26 for feature selection for email.…”
Section: Introductionmentioning
confidence: 99%
“…e work presented by [30] proposes an automated breast cancer diagnosing system by employing the GVFSnake Segmentation method, the wavelet-based feature extraction, and the fuzzy-based classification. A hybrid optimization algorithm-based feature selection for mammogram images and hybrid transfer learning for detecting the breast masses of mammographs are presented by [31,32]. e authors in [33] proposed a novel computer-aided diagnosis (CAD) system based on one of the regional deep learning techniques, an ROI-based convolutional neural network for simultaneous detection and classification of breast masses in digital mammograms.…”
Section: Literature Review and Related Workmentioning
confidence: 99%